Production Of Hydrochar-Based Catalyst From Oil Palm Trunk Via Hydrothermal Carbonization - Tan, Wee Hui (Universiti Sains Malaysia, 2022)
Oil palm trunk (OPT) is one of the most abundant wastes from the oil palm plantation. In order to manage the oil palm trunk, it can be utilized to produce biofuel or bio-based products. The utilization of oil palm trunk can be achieved by various thermochemical conversion process. Among the thermochemical conversion processes, hydrothermal carbonization (HTC) is eco-friendly process which treats raw biomass in the presence of water at elevated temperature. Through a series of reaction mechanisms, including hydrolysis, dehydration, decarboxylation, decarbonylation, polymerization and re-condensation, solid hydrochar is generated. The objective of this study is to produce hydrochar and hydrochar-based catalyst from oil palm trunk via hydrothermal carbonization (HTC). The temperature and residence time of HTC process were varied at 180 ℃ and 220 ℃ under three residence times; 0.5 hour, 1 hour and 2 hours and the effects on the yield of hydrochar were studied. It was observed that the reaction temperature has a greater effect on the hydrochar yield as compared to the residence time. The optimized condition for hydrochar yield (48.77 %) was found at 180 ℃ with the residence time of 1 hour. Impregnation of hydrochar with potassium hydroxide (KOH) was carried out to study the possibility of using the produced hydrochar as a support for catalyst. Fourier Transform Infra-Red (FTIR), Thermo-gravimetric (TGA) Analysis, Brunauer-Emmett-Teller (BET) and Scanning Electron Microscope (SEM) were carried out to characterize the raw OPT, hydrochar and hydrochar-based catalyst. SEM analysis revealed that the HTC process has altered the structure of oil palm trunk significantly to become hydrochar with a porous surface, while impregnation of KOH has altered the surface of hydrochar to become more uneven and irregular. Moreover, the BET surface area of hydrochar increased after HTC process. Besides, FTIR analysis shows that the functional groups for both raw oil palm trunk and hydrochar is basically the same, but slightly different from hydrochar-based catalyst. The TGA analysis revealed that weight loss kinetics was likely similar for all of them. Based on these results, properties of hydrochar varied according to temperatures, residence time as well as the impregnation of KOH. Therefore, the temperature, residence time and impregnation method significantly affect the production of hydrochar and its catalytic application.